1983
DOI: 10.1111/j.1365-2265.1983.tb03181.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroxinaemia: Abnormal Binding of T4 by an Inherited Albumin Variant

Abstract: Two euthyroid subjects with high total concentrations of T4 in their sera have been studied (J.D.: T4, 170; T3, 1.90; rT3, 0.54 nmol/l. E.T.: T4, 185; T3, 1.63; rT3, 0.37 nmol/l). Concentrations of all three T4-binding proteins were within normal limits in both cases. However, on reverse-flow electrophoresis an abnormally large amount of thyroxine was found to travel with albumin. The three T4-binding proteins in the sera of both patients were separated from each other by a novel affinity chromatographic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Although this condition had been widely reported in the medical literature (1)(2)(3)(4)(5)(6)(7)(8), the molecular basis of FDH was not known until the identification of a single point mutation in the HSA gene of several FDH individuals resulting in the substitution of histidine for arginine at amino acid position 218 (9). This result was confirmed by another study in which the same mutation was identified in FDH individuals from eight unrelated families (10).…”
supporting
confidence: 75%
“…Although this condition had been widely reported in the medical literature (1)(2)(3)(4)(5)(6)(7)(8), the molecular basis of FDH was not known until the identification of a single point mutation in the HSA gene of several FDH individuals resulting in the substitution of histidine for arginine at amino acid position 218 (9). This result was confirmed by another study in which the same mutation was identified in FDH individuals from eight unrelated families (10).…”
supporting
confidence: 75%
“…Although earlier studies based on electrophoretic, chemical, and immunological properties have associated the TT 4 abnormality to a HSA variant (Lee et al, 1979;Stockigt et al, 1981;Silverberg and Premachandra, 1982;Lalloz et al, 1983;Weiss et al, 1995), the precise defect was identified only in 1994 (Petersen et al, 1994;Sunthornthepvarakul et al, 1994). In particular, the missense mutation Arg218His produces a HSA variant (named FDH-2) with 10-to 15-fold higher affinity for T 4 than the wild-type molecule, and a 5-fold increase in affinity for T 3 (Sunthornthepvarakul et al, 1994;Petersen et al, 1996;Petitpas et al, 2003).…”
Section: Familial Dysalbuminemic Hyperthyroxinemia and Familial Dysalmentioning
confidence: 95%
“…The total tri-iodothyronine (T 3 ) (tT 3 ) and thyroidstimulating hormone (TSH) concentrations, usually, are normal (1)(2)(3)(4)(5)(6). These discrepancies are due to the presence of an abnormal serum albumin that exhibits enhanced binding of T 4 , and patients with FDH are clinically euthyroid (7)(8)(9)(10). Although FDH has been widely reported in the medical literature and accounts for the most common cause of genetic euthyroid hyperthyroxinemia in western countries, particularly among hispanics of Puerto Rican origin (11)(12)(13), to our knowledge no case has been reported in individuals of Chinese or African origin.…”
Section: Introductionmentioning
confidence: 99%